Hip surgery : An odyssey - Sarmiento, Augusto (New Delhi Jaypee Brothers Medical Publishers, 2012)
Hip Surgery: An Odyssey is a step by step journey through important technological developments in hip surgery. Based on the author's personal experiences, the book examines past and present procedures, their successes and complications. Enhanced by more than 600 well-illustrated images, this text discusses different types of hip surgery - reconstructive surgery, including total hip arthroplasty; specific pathological conditions, the fractured hip and annexures.
Cirugía de Cadera: Una Odisea es un viaje paso a paso a través de importantes desarrollos tecnológicos en cirugía de cadera. Basado en las experiencias personales del autor, el libro examina los procedimientos pasados ​​y presentes, sus éxitos y complicaciones. Mejorado con más de 600 imágenes bien ilustradas, este texto analiza diferentes tipos de cirugía de cadera: cirugía reconstructiva, incluida la artroplastia total de cadera; condiciones patológicas específicas, la fractura de cadera y anexos.
Contents Section 1. Reconstructive surgery Section 2. Specific pathological conditions Section 3. The fractures hip Section 4. Annexuries
Keywords: CIRUGÍA DE CADERA; CADERA -- FRACTURAS; ENFERMEDAD TROMBOEMBÓLICA